(untitled) (The International Journal for Scientific Research, 2025)
The study aimed to identify the professional and ethical challenges of investigative journalism and its relationship to journalistic practice, relying on the media survey approach, by conducting a field survey on an available sample of (240) male and female journalists practicing journalism in press and media institutions in Jordan, by relying on the gatekeeper theory, and the approach of pressures and professional practices. The results of the study showed that (63.7%) of Jordanian journalists did not practice investigative journalism in their journalistic work, while the most prominent reasons for not practicing investigative journalism were: lack of interest in investigative journalism (26.9%), lack of freedom in investigative journalism (19.6%), and low level of experience sufficient to practice investigative work. The results showed that the most prominent professional and ethical challenges of investigative journalism were challenges related to the use of digital technology with mean of (4.39), then challenges of professional ethics (4.36), then professional principles (4.34), then editorial policy (4.03), then methods of managing and organizing journalistic work (4.21), and the results concluded that there is a statistically significant positive correlation between the impact of the professional and ethical challenges of investigative journalism, and the professional principles that investigative journalists adhere to.